1974
DOI: 10.1128/aac.5.5.447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethylenediaminetetraacetic Acid and Related Chelating Agents on Whole Cells of Gram-Negative Bacteria

Abstract: The effects of ethylenediaminetetraacetic acid and of four other chelating agents on seven strains of gram-negative bacteria are described. Changes in viability, cell lysis, and release of intracellular materials from suspensions in various buffers, pH 7.8 or 9.2, were observed. Cyclohexane-1,2-diaminotetraacetic acid was the most toxic compound, whereas iminodiacetic acid and nitrilotriacetic acid had little bactericidal activity. The activity of the five drugs appeared to be related to their chelating abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Since sodium tripolyphosphate is a chelating agent, it is plausible, as with other chelators such as EDTA, that this antibacterial activity occurs by disruption of the bacterial cell envelope through the sequestration of stabilizing divalent cations. Such cations normally link bacterial lipopolysaccharides to the outer membrane and interference with this process can destabilize the outer membrane in Gram-negative bacteria, impairing barrier function (50,51,52). Furthermore, strong chelating agents may inhibit bacterial growth by sequestering trace minerals required for bacterial metabolism (51,53).…”
Section: Discussionmentioning
confidence: 99%
“…Since sodium tripolyphosphate is a chelating agent, it is plausible, as with other chelators such as EDTA, that this antibacterial activity occurs by disruption of the bacterial cell envelope through the sequestration of stabilizing divalent cations. Such cations normally link bacterial lipopolysaccharides to the outer membrane and interference with this process can destabilize the outer membrane in Gram-negative bacteria, impairing barrier function (50,51,52). Furthermore, strong chelating agents may inhibit bacterial growth by sequestering trace minerals required for bacterial metabolism (51,53).…”
Section: Discussionmentioning
confidence: 99%
“…Agar plates containing concentrations of 0 to 2 ,ug of cetrimide, benzalkonium chloride, and chlorhexidine per ml were "spotted" with low numbers of viable cells of each organism, and the colonies were counted after incubation. Counts on drug-containing plates were not significantly different from those on control plates (no drug present), and it was concluded that the concentrations in agar of cetrimide, benzalkonium chloride, and chlorhexidine should not exceed 2 ,ug/ml. In the actual viable counting for determining survivor levels (below), levels of these compounds in agar were 1/106 of those used in Tables 2 to 5 and thus were negligible.…”
Section: Mics Of the Antibacterial Agents Thementioning
confidence: 99%
“…This slow initial rate of death could be related to the magnitude of the effect of the chelating agent. The two P. aeruginosa strains are the most susceptible to EDTA and related substances (2), and thus pretreated cells would be expected to be killed most rapidly by a sublethal drug concentration; strain Kl is the most resistant to these chelating agents (2), and thus pretreated cells would be expected to be killed least rapidly by such a drug concentration. These, in fact, occur (Tables 2-4), and it is thus tempting to speculate that cell wall cations, by virtue of their binding effect, are involved to considerable extent in cell resistance.…”
Section: Mics Of the Antibacterial Agents Thementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the formulation included chelating agents such as sodium tripolyphosphate, which may, as is the case with many chelators, have antimicrobial activity due to its ability to disrupt the bacterial cell envelope (39). This may occur through the sequestering of stabilizing divalent cations, causing the release of lipopolysaccharides from the cell envelope and consequently impairing barrier function (40,41). This provides a plausible explanation for the heightened antimicrobial activity observed with the BAC formulation compared to the simple aqueous BAC solution.…”
Section: Discussionmentioning
confidence: 99%